KEBERADAAN POLISI SANTRI DALAM ORGANISASI KEPOLISIAN RESOR DI KOTA PALOPO - Ilham Laman (Universitas Islam Negeri Alauddin Makassar, 2020)
The police are one government agency established to maintain security and public order, as well as provide security and peace for the community. This role is carried out based on Law number 2 of 2002. This role is then leading to defining the vision and mission of the police as an institution to protect, guide, and serve the public, as well as to enforce the law. Accordingly, the police strive to create innovations for society by applying several programs to maintain their duties. For instance, both the city police of Palopo and the regional police of Sulawesi Selatan initiate a program called “Polisi Santri” referring to the group of police officers who have adequate Islamic knowledge in the institution. This program aims to make people feel secure and to enhance their spiritual knowledge. Besides, it also becomes an alternative for the criminals who will be guided based on Islamic teachings and approaches to prevent them for doing the same mistakes, to create a safe environment, and to prevent any disturbances in the community